Nichrome Dependency in Welding Layer Using In situ Fabrication on Hardness and Corrosion Properties - Syaripuddin; Sopiyan; Muhammad Fauzan Perdana Putra; Maman Kartaman Ajiriyanto; Sigit Dwi Yudanto; Muhammad Yunan Hasbi; Susetyo, Ferry Budhi (Science and Technology Indonesia, 2024)
The use of shielded metal arc welding (SMAW) equipment to synthesize alloys is one of the most promising methods as it can be used for in-situ fabrication. The hardness and corrosion properties of the deposited layer during the welding process can be enhanced by dilution of nichrome (NiCr) during the process. Therefore, the alloy was synthesized on the surface of the mild steel using SMAW equipment with various NiCr additions. The properties of the alloy were investigated using an X-ray diffraction (XRD), an Optical microscope, a Potentiostat, and a Vickers hardness apparatus. The appearance of martensite overlaps with the ferrite phase could be affected by the addition of NiCr to the alloy. An increase in NiCr content is followed by an increase in the lattice parameter value of the ferrite phase. The presence of a certain amount of nickel (Ni) contributes to the formation of lower transformation phases, including martensite. At the same time, the incorporation of chromium (Cr) also plays a significant role in promoting the formation of acicular ferrite. An increase in NiCr content in NiCr2 and NiCr3 samples results in a quantitative increase in martensite formation. Adding 0.434 g of NiCr to the weld deposited layer could result in the corrosion rate of the alloy being 0.1118 mm/y. Higher hardness is found in the NiCr3 sample, around 742.06 HV.